Impact sourcing initiatives in Malaysia: an insight through porter’s diamond framework - Ismail, Shahifol Arbi; Aman, Aini (Springer, 2017)
The aim of this study is to understand the key resources needed to ensure successful impact sourcing (ImS) initiatives in Malaysia. In this study, ImS refers to the effort of creating employment opportunities to marginalized communities by bringing simple, low-value outsourcing tasks to the communities. Using Porter’s Diamond Framework in ImS initiatives in Malaysia, we identified the availability of good ICT infrastructure, vibrant presence of SSO firms, and strong government support as key enablers of ImS in Malaysia. The challenges for ImS success in Malaysia include low English proficiency and high attrition rates among ImS workers and absence of micro-payments providers. Nevertheless, such challenges could be overcome by realizing the potential of ImS with full government support. These findings contribute to the formulation of potential strategies and policies in ensuring the growth of ImS in Malaysia.